Fabrication of PVDF hollow fiber membranes via integrated phase separation for membrane distillation - Li, Y.; Jin, C.; Peng, Y.; An, Q.; Chen, Z.; Zhang, J.; Ge, L.; Wang, Shaobin (2019)
© 2018 Taiwan Institute of Chemical Engineers In this study, polyvinylidene fluoride (PVDF) hollow fibers with interpenetrating network morphologies were fabricated via complex thermally induced phase separation (c-TIPS) by integration of non-solvent induced phase separation (NIPS) and thermally induced phase separation (TIPS) at 80 °C and then tested in membrane distillation (MD). The effects of solvents, additive and bore fluid on the membrane morphology, pore structure and MD performance were investigated. Direct-contact membrane distillation (DCMD) for desalination was carried out to evaluate membrane permeability and salt rejection. Using a weak solvent like triethylphosphate (TEP) and weak bore fluid like polyethylene glycol (PEG-200) in the c-TIPS favors the formation of an interpenetrating network morphology. In addition, PEG-200 increased the roughness and water contact angle of the inner skin. The hollow fibers fabricated via the c-TIPS at low temperature presented high permeability, mechanical strength and long-term stability. In desalination of formulated seawater, a distillate flux of 61.6 kg/m2h with NaCl rejection of 99.99% was achieved at feed temperature of 71 °C.